A dinâmica da ciência e da tecnologia nos intercâmbios entre Brasil e China: o caso dos Institutos Confúcio - Martinelli, Marina (Universidade Federal de São Carlos, 2020)
THE DYNAMICS OF SCIENCE AND TECHNOLOGY IN EXCHANGES BETWEEN BRAZIL AND CHINA: THE CASE OF CONFUCIO INSTITUTES IN BRAZIL This work addressed the topic of academic exchange between Brazil and China, specifically the case of Confucius Institutes in Brazil, through the investigation of the experiences of UNESP and UNICAMP. The objective was to understand how CIs contribute to academic exchange in the area of economic and cultural cooperation between Brazil and China and how these particular relations contribute to the social stratification of those two countries, affecting Brazil's social structure in particular. In the other hand, understanding how the dynamics of Science and Technology works in the production of a globalized elite that will lead a new way of acting, which will influence the direction of the future of life in society. The instruments through which these young people are working and how to democratize this category were studied through the Confucius Institutes. In this research, bibliographic and bibliometric research was done; the websites of the CIs of UNESP and UNICAMP were analyzed; documents produced by the CIs were analyzed; a questionnaire was applied for semi-structured interviews with the directors of CIs, key people and exchange students, through a multi-method methodology, which combines quantitative and qualitative researches, through a macrophysical and microphysical look. The justification is found in the political, cultural and economic movement provided by Brazil - China relations, through the BRICS. The Ciência Sem Fronteiras, Idioma Sem Fronteiras and Paraná Fala Inglês programs were studied because they are the most recent models of Brazilian exchange, although CIs are closely linked to programs such as those of the Goethe and Cervantes Institute, only institutionally, rooted in the universities. Brazil has 12 CIs and none of them intends to indoctrinate Confucianism, but rather to spread the Mandarin language, therefore, the experience has demonstrated the importance of a truly bilateral assessment of tasks in the face of Chinese soft power.
The dynamics of science and technology in exchanges between Brazil nad China: the caso of Confucius Institute
Keywords: Ciência; Tecnologia e sociedade; Institutos Confúcio; Intercâmbio Brasil-China; Soft power; Science; Technology and society; Confucius institutes; Brazil-China exchange; CIENCIAS HUMANAS